Surface Acoustic Wave Propagation Using Crawling Waves Technique in High Frequency Ultrasound - Saavedra, AC (2018)
Several tropical diseases generate cutaneous lesions on the skin with different elastic properties than normal tissue. A number of non-invasive elastography techniques have been created for detecting the mechanical properties in tissue in the last decades. Quantitative information is mainly obtained by harmonic elastography, which is distinguished for producing shear wave propagation. When wave propagation is near a boundary region, surface acoustic waves (SAW) are found. This work presents crawling waves elastography technique implemented with a high-frequency ultrasound (HFUS) system for the estimation of SAW speed and its relationship with the elastic modulus. Experiments are conducted to measure SAW speed in a homogeneous phantom with a solid-water interface for a theoretical validation. Afterwards, ex-vivo experiments in thigh pork were performed to show SAW propagation in animal tissue. Preliminary results demonstrate the presence of SAW propagation in phantoms and skin tissue and how wave speed should be correctly adjusted according to the coupling media for elastography applications. © 2018, Springer International Publishing AG.